Current status and future prospects of pretreatment for tobacco stalk lignocellulose - Hu, Nianwu; Liu, Xiongbin; Wei, Shuoguo; Yao, Jianwu; Wang, Wanxia; Liu, Ben; Tang, Tianming; Jiang, Jungang; Wang, Lei (Frontiers in Bioengineering and Biotechnology, 2024)
With the growing demand for sustainable development, tobacco stalks, as a resource-rich and low-cost renewable resource, hold the potential for producing highvalue chemicals and materials within a circular economy. Due to the complex and unique structure of tobacco stalk biomass, traditional methods are ineffective in its utilization, making the pretreatment of tobacco stalk lignocellulose a crucial step in obtaining high-value products. This paper reviews recent advancements in various pretreatment technologies for tobacco stalk lignocellulosic biomass, including hydrothermal, steam explosion, acid, alkaline, organic solvent, ionic liquid, and deep eutectic solvent pretreatment. It emphasizes the impact and efficiency of these pretreatment methods on the conversion of tobacco stalk biomass and discusses the advantages and disadvantages of each technique. Finally, the paper forecasts future research directions in the pretreatment of tobacco stalk lignocellulose, providing new insights and methods for enhancing its efficient utilization.